Just-in-Time Teaching in Statistics Classrooms. Issue 1 (2nd January 2016) - McGee, Monnie; Stokes, Lynne; Nadolsky, Pavel
ABSTRACT: Much has been made of the flipped classroom as an approach to teaching, and its effect on student learning. The volume of material showing that the flipped classroom technique helps students better learn and better retain material is increasing at a rapid pace. Coupled with this technique is active learning in the classroom. There are many ways of "flipping the classroom." The particular realization of the flipped classroom that we discuss in this article is based on a method called "Just-in-Time Teaching (JiTT)." However, JiTT, in particular, and the flipped classroom, in general, is not just about watching videos before class, or doing activities during class time. JiTT includes assigning short, web-based questions to students based on previously viewed material. Typically, Internet-based questions are constructed to elicit common misunderstandings from the students, so that the instructor can correct such misunderstandings immediately in the next class period, hence the name, "Just-in-Time Teaching." The addition of these pre-class questions is what separates JiTT from a general flipped classroom model. Even as the research on the superiority of JiTT as a learner-centered pedagogical method mounts, aids for the instructor have not, at least not as quickly. This article is focused on the instructor—with aids to help the instructor begin using the JiTT flipped classroom model in statistics courses.